Location of largest earthquake slip and fast rupture controlled by along‐strike change in fault structural maturity due to fault growth. Issue 5 (20th May 2016) - Perrin, Clément; Manighetti, Isabelle; Ampuero, Jean‐Paul; Cappa, Frédéric; Gaudemer, Yves
Abstract: Earthquake slip distributions are asymmetric along strike, but the reasons for the asymmetry are unknown. We address this question by establishing empirical relations between earthquake slip profiles and fault properties. We analyze the slip distributions of 27 large continental earthquakes in the context of available information on their causative faults, in particular on the directions of their long‐term lengthening. We find that the largest slips during each earthquake systematically occurred on that half of the ruptured fault sections most distant from the long‐term fault propagating tips, i.e., on the most mature half of the broken fault sections. Meanwhile, slip decreased linearly over most of the rupture length in the direction of long‐term fault propagation, i.e., of decreasing structural maturity along strike. We suggest that this earthquake slip asymmetry is governed by along‐strike changes in fault properties, including fault zone compliance and fault strength, induced by the evolution of off‐fault damage, fault segmentation, and fault planarity with increasing structural maturity. We also find higher rupture speeds in more mature rupture sections, consistent with predicted effects of low‐velocity damage zones on rupture dynamics. Since the direction(s) of long‐term fault propagation can be determined from geological evidence, it might be possible to anticipate in which direction earthquake slip, once nucleated, may increase, accelerate, and possibly lead to a large earthquake. Our results could thus contribute to earthquake hazard assessment and Earthquake Early Warning. Key Points: Earthquake slip asymmetry relates to along‐strike changes in fault properties due to fault growth Largest slip and faster rupture speed systematically occur on most mature half of ruptured fault sections Larger slip is promoted by greater off‐fault compliance and lower fault strength in mature parts